Cat scratch disease, a rare cause of hypodense liver lesions, lymphadenopathy and a protruding duodenal lesion, caused by Bartonella henselae. (29th October 2014) - van Ierland-van Leeuwen, Marloes; Peringa, Jan; Blaauwgeers, Hans; van Dam, Alje
Abstract : A 46-year-old woman presented with right upper abdominal pain and fever. At imaging, enlarged peripancreatic and hilar lymph nodes, as well as hypodense liver lesions, were detected, suggestive of malignant disease. At endoscopy, the mass adjacent to the duodenum was seen as a protruding lesion through the duodenal wall. A biopsy of this lesion, taken through the duodenal wall, showed a histiocytic granulomatous inflammation with necrosis. Serology for Bartonella henselae IgM was highly elevated a few weeks after presentation, consistent with the diagnosis of cat scratch disease. Clinical symptoms subsided spontaneously and, after treatment with azithromycin, the lymphatic masses, liver lesions and duodenal ulceration disappeared completely.